Методология вибромониторинга расходования ресурсов редукторов мотор-колес большегрузных самосвалов - Ишин, Н. Н.; Гаврилов, С. А. (НТУ "ХПИ", 2011)
Предложена методология расчетно-экспериментального определения остаточного ресурса зубчатых передач при испытаниях и в эксплуатации, основанная на мониторинге их вибрационных характеристик. Описана бортовая система вибромониторинга редукторов мотор-колес самосвала БелАЗ.

The methodology of experiment-calculated prediction of residual life of the car’s gearings and driven devices in process of tests and exploitation is expounded. It is based on monitoring and analysis of their vibration characteristics. The device and principle of operation of the on-board vibromonitoring system of the gearboxes of motor-in-wheel of dump truck BelAZ are described.
The methodology of the resources expending vibromonitoring of the large trucks power-wheels gearings
Keywords: зубчатые передачи; остаточный ресурс; ресурсные испытания; РМК; аналого-цифровой преобразователь